BahaKajian aspek keamanan nyamuk Aedes aegypti Linnaeus ber-Wolbachia di Yogyakarta, Indonesiasa Indonesia: Assessing the safety of Wolbachia-infected Aedes aegypti Linnaeus mosquitoes in Yogyakarta, Indonesia - Saraswati, Utari; Supriyati, Endah; Rahayu, Ayu; Rovik, Anwar; Kurniasari, Irianti; Hermantara, Rio; Kumalawati, Dian Aruni; Daniwijaya, Edwin Widyanto; Fitriana, Iva; Pramuko, Nida Budiwati; Indriani, Citra; Wardana, Dwi Satria; Tantowijoyo, Warsito; Ahmad, Riris Andono; Utarini, Adi; Arguni, Eggi (Perhimpunan Entomologi Indonesia, 2023)
Dengue prevention efforts are limited to the control strategies of its vector and the management of breeding sites. New alternatives for dengue vector control that are sustainable and more environmentally friendly are needed to complement the government's current efforts. Research on Wolbachia-infected Aedes aegypti Linnaeus mosquitoes as an alternative biocontrol strategy has been performed in Yogyakarta City. However, one of the concerns of the community members and stakeholders about this technology is the safety aspect regarding the transmission of Wolbachia to other species and the possibility that humans will contract Wolbachia. This study aimed to address these concerns, namely to find out whether horizontal transmission of Wolbachia occurred from A. aegypti that were released to other species and whether residents living in the released areas were infected with Wolbachia. The research was conducted in Dusun Nogotirto and Dusun Kronggahan (Sleman Regency), as well as in Dusun Jomblangan and Dusun Singosaren (Bantul Regency), Yogyakarta Special Province. Wolbachia qPCR screening using the target gene WD0513 was performed on 922 Culex quinquefasciatus Say and 331 Aedes albopictus (Skuse). ELISA test was carried out on 190 pairs of plasma samples, namely the sample before the Wolbachia frequency was established (still <80%) and the sample after it was established (>80%). The results showed no evidence of Wolbachia transfer from Wolbachia-infected A. aegypti to other mosquito species coexisting in the same habitat or to humans. This study corroborates the safety evidence of Wolbachia-infected A. aegypti technology as an alternative to control dengue virus transmission